ANALISIS PERUBAHAN PERILAKU SOSIAL MASYARAKAT SETELAH DIBANGUNNYA TAMAN ALUN-ALUN GUNUNG GAJAH DI PEMANGKAT - Purnama, Indah; Bahari, Yohanes; Ismiyani, Nining (Universitas Tanjungpura, 2022)
AbstractThis study aims to determine the social behavior of the community after theconstruction of the Gunung Gajah Square Park in Pemangkat, Pemangkat KotaDistrict, Sambas Regency, West Kalimantan. The general problem in thisresearch is social behavior changes in the form of cooperation and respect forthe community after the construction of the Gunung Gajah Square Park inPemangkat. The method used in this research is descriptive in the form ofqualitative research. Data collection techniques used are observation,interviews and documentation. The data collection tools used are observationguides, interview guides and documentation. There are 4 informants from thecommunity who live in Gunung Gajah Park Square in Pemangkat, PemangkatKota District, Sambas Regency. Analysis of research data is presented in aqualitative descriptive manner. The results of this study indicate that socialbehavior in the form of cooperation and respect is still well established and afterthe construction of the Gunung Gajah Square Park added a sense of unity tohelp respect the local residents and take care of each other in the Gunung GajahPark Square in Pemangkat.Keywords: Change, Social Behavior, Society, Taman Alun-alun Gunung Gajah